1997
DOI: 10.1126/science.278.5345.1931
|View full text |Cite
|
Sign up to set email alerts
|

Atomic and Macroscopic Reaction Rates of a Surface-Catalyzed Reaction

Abstract: The catalytic oxidation of carbon monoxide (CO) on a platinum (111) surface was studied by scanning tunneling microscopy. The adsorbed oxygen atoms and CO molecules were imaged with atomic resolution, and their reactions to carbon dioxide (CO2) were monitored as functions of time. The results allowed the formulation of a rate law that takes the distribution of the reactants in separate domains into account. From temperature-dependent measurements, the kinetic parameters were obtained. Their values agree well w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
236
0
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 352 publications
(240 citation statements)
references
References 17 publications
3
236
0
1
Order By: Relevance
“…5 were obtained for oxygen adsorbed on Pt(111) at 300 K (a) and 500 ± 50 K (b). Figure 5a and b both show the same p(2 9 2) structure of 0.25 ML of adsorbed atomic oxygen known from previous STM studies [13,14]. This means that, although TPD data in Fig.…”
Section: Resultsmentioning
confidence: 70%
“…5 were obtained for oxygen adsorbed on Pt(111) at 300 K (a) and 500 ± 50 K (b). Figure 5a and b both show the same p(2 9 2) structure of 0.25 ML of adsorbed atomic oxygen known from previous STM studies [13,14]. This means that, although TPD data in Fig.…”
Section: Resultsmentioning
confidence: 70%
“…Examples include: (i) exposure of an oxygen pre-covered Pt(1 1 1) surface to CO [14,15], (ii) exposure of a CO precovered Pt(1 1 1) surface to high pressure O 2 [16], and (iii) time-dependent reactivity studies of Pt(1 1 0) under large and small CO/O 2 pressure ratios [2]. In case (i), the surface was found to accommodate two coexisting adsorbate phases, c(4 · 2)-2CO, and p(2 · 2)-(O + CO), in case (ii) vacancies in the saturated CO adsorption phase were found to be necessary during transient reaction conditions, and in case (iii), an oxide phase was shown to be growing during steady state reaction conditions.…”
Section: Structure Of Three-phase Boundarymentioning
confidence: 99%
“…For instance, it has been observed that oxygen and CO do not simply adsorb on random surface sites but rather they coalesce to form islands of CO and O species [58,85]. The actual reaction between CO and O is thought to take place at the edges of these islands.…”
Section: Carbon Monoxide Oxidationmentioning
confidence: 99%
“…The crucial assumption in this framework is that all the species adsorb prior to engaging in a reaction and are distributed evenly over the surface, which consists of identical catalytic sites. It is known that in practice for some reactions, such as CO oxidation, the adsorbates actually form islands rather than distribute evenly [58]. Effects such as island formation and differences between site types are neglected.…”
Section: Langmuir-hinshelwood Reaction Schematicsmentioning
confidence: 99%